2016
DOI: 10.1007/s12028-016-0332-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value of Neutrophil to Lymphocyte and Platelet to Lymphocyte Ratio After Aneurysmal Subarachnoid Hemorrhage

Abstract: NLR and PLR as novel inflammatory biomarkers are independent predictors of DCI development and functional outcome after acute aSAH. When combined together, they may help to identify high-risk patients more powerfully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(96 citation statements)
references
References 39 publications
3
92
1
Order By: Relevance
“…Recently, in some ICH-studies, NLR has been associated with clinical endpoints [2,12,[16][17][18][19] . However, in ICH patients, little is known about the natural course of systemic inflammation during hospital stay and whether NLR is associated with short-term mortality.…”
Section: Neutrophil-to-lymphocyte Ratio Is Anmentioning
confidence: 99%
“…Recently, in some ICH-studies, NLR has been associated with clinical endpoints [2,12,[16][17][18][19] . However, in ICH patients, little is known about the natural course of systemic inflammation during hospital stay and whether NLR is associated with short-term mortality.…”
Section: Neutrophil-to-lymphocyte Ratio Is Anmentioning
confidence: 99%
“…In a recent study NLR and PLR were found as independent predictors of delayed cerebral ischemia development and worse functional outcome after acute aneurysmal SAH (10). Taken together, all these results indicate that inflammation at least partially mediates the linkage between the short term mortality of SAH with lymphopenia, NLR and PLR.…”
Section: Discussionmentioning
confidence: 69%
“…NLR and PLR are novel composite inflammatory markers in the area of vascular pathologies including cerebral iscemia, intracerebral hemorrhage, venous thromboembolism (10,11,17). It has been also shown that increased platelet activation plays an important role in the initiation and progression of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Buck [9] demonstrated the higher NLR was associated with larger infarct volumes in patients with AIS, rather than lymphocyte counts. Recently, the platelet to lymphocyte ratio (PLR) was considered as a novel predictor for functional outcomes in patients with stroke [36,37]. Until now, there was one study [36] regarding the influence of PLR to ischemic stroke, with a sensitivity of 73% and specificity of 69%, however, this study had the limited number of patients without multivariate regression analysis.…”
Section: Figurementioning
confidence: 99%